PENGARUH Trichoderma asperellum DAN KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH VARIETAS LEMBAH PALU (Allium L.x Wakegi Araki) - Kasman Jaya; Idris Idris; Yuliana (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
This study aims to determine the effect of giving T. asperellum and compost on the growth and yield of shallots of the Palu Valley variety. This research was conducted on July to September 2019 in Oloboju Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi Province. This research is a kind of experimental research that is designed by using a Randomized Group Design with grouping based on watering time. The treatments tested consisted of: P0 = Control (without treatment), P1 = T. asperellum 48g + 12 liters of water, P2 = T. asperellum 48g + 12kg compost and P3 = 12kg compost. To determine the effect of the treatment being tried, a diversity test was conducted. If the diversity test results show a real influence, then proceed with the Honestly Significant Difference test (BNJ) α = 0.05 to find out the differences between treatments. Treatment of various combinations of T. asperellum and compost significantly affected plant height at ages 15 and 25 HST, but had no significant effect on the number of leaves, leaf fresh weight, root fresh weight, leaf dry weight, root dry weight, number of tubers per clump, fresh tuber weight per clump, fresh tuber weight per plot and fresh tuber weight per hectare. The compost treatment gives a better effect on the height of plants aged 15 HST (average 15.09cm) and 25 HST (average 19.86cm).